2020
DOI: 10.1080/09546634.2020.1801977
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs in patients with moderate-to-severe plaque psoriasis treated with methotrexate in real world practice: FirST study

Abstract: Background: Methotrexate (MTX) is frequently used in the treatment of moderate-to-severe psoriasis, however, there is limited data on health-related quality-of-life (HRQoL), psoriasis clinical outcomes and hepatic fibrosis in MTX-treated patients in routine clinical practice. Objectives: To investigate the impact of moderate-to-severe psoriasis in MTX-treated patients in Spain regarding to HRQoL, psoriasis clinical data and risk of hepatic fibrosis. Methods: Observational, non-interventional, cross-sectional, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…We included thirty-seven studies in the quantitative analysis ( 19 , 27 62 ), and twelve studies were only used qualitatively ( 55 – 66 ). Nine types of NIT were included: twenty-two TE ( 27 , 29 – 34 , 36 42 , 44 46 , 48 , 49 , 51 – 53 , 66 ) ( n = 2222), thirteen PIIINP ( 36 , 54 65 ) ( n = 947), six FIB-4 ( 19 , 27 , 28 , 32 , 34 , 35 ) ( n = 689), five NAFLD fibrosis score (NFS) ( 28 , 32 , 34 , 35 , 47 ) ( n = 477), four FibroTest/FibroSure ( 34 , 43 , 50 , 66 ) ( n = 285), two AST to Platelet Ratio Index (APRI) ( 27 , 34 ) ( n = 180), two Enhanced Liver Fibrosis score (ELF) ( 54 , 65 ) ( n = 297), one Forns Index ( 34 ) ( n = 63), one FibroMeter ( 34 ) ( n = 64), one Hepascore ( 34 ) ( n = 64), and one Fibrosis Probability Index ( 34 ) ( n = 64) studies. Formulae of NITs mentioned in this review are shown in Supplementary Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…We included thirty-seven studies in the quantitative analysis ( 19 , 27 62 ), and twelve studies were only used qualitatively ( 55 – 66 ). Nine types of NIT were included: twenty-two TE ( 27 , 29 – 34 , 36 42 , 44 46 , 48 , 49 , 51 – 53 , 66 ) ( n = 2222), thirteen PIIINP ( 36 , 54 65 ) ( n = 947), six FIB-4 ( 19 , 27 , 28 , 32 , 34 , 35 ) ( n = 689), five NAFLD fibrosis score (NFS) ( 28 , 32 , 34 , 35 , 47 ) ( n = 477), four FibroTest/FibroSure ( 34 , 43 , 50 , 66 ) ( n = 285), two AST to Platelet Ratio Index (APRI) ( 27 , 34 ) ( n = 180), two Enhanced Liver Fibrosis score (ELF) ( 54 , 65 ) ( n = 297), one Forns Index ( 34 ) ( n = 63), one FibroMeter ( 34 ) ( n = 64), one Hepascore ( 34 ) ( n = 64), and one Fibrosis Probability Index ( 34 ) ( n = 64) studies. Formulae of NITs mentioned in this review are shown in Supplementary Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Although some studies associate methotrexate liver toxicity with cumulative dose and treatment time, most find that the risk of liver damage is primarily related to the presence of risk conditions such as obesity, DM2, alcohol consumption, and NAFLD[ 80 , 81 ]. Cyclosporine and acitretin, a retinoid derived from vitamin A, are considered to be diabetogenic and to promote atherogenic dyslipemia and arterial hypertension[ 79 , 82 ].…”
Section: Nafld and Psoriasismentioning
confidence: 99%
“…A study conducted in Spain in patients (n = 497) treated with MTX found that 64.1% had hepatic steatosis. Moreover, based on the NAFLD fibrosis score and the Fibrosis-4 Index for Liver Fibrosis score, 37.2%, and 26.2%, respectively, were considered to have an intermediate-to-high risk of developing liver fibrosis, which was also associated with a longer duration of treatment [ 24 ].…”
Section: Introductionmentioning
confidence: 99%